Influence of atmospheric conditions on the incidence of atrial fibrillation - Katarzyna Sawicka; Marek Prasał; Agnieszka Wawryniuk; Robert Jan Łuczyk; Magdalena Szych; Marta Łuczyk; Jadwiga Daniluk (Kazimierz Wielki University, 2017)
Admission. Atrial fibrillation is the most commonly encountered arrhythmia today. The risk of her occurrence increases with age. Atrial fibrillation is associated with serious complications, mainly thromboembolic disease, which is therefore a significant clinical problem. Changing weather conditions have a major impact on the well-being of people, especially the circulatory system. Poland is located in the place where wet and dry air masses are abrasive, which causes sudden changes in weather. Material and method. The study was conducted by the diagnostic survey method. The information needed to carry out the study was obtained using the author's questionnaire. The questionnaire consisted of a metric section containing questions about age, sex, place of residence and education. The study was conducted among patients in the Intensive Care Unit of the Independent Public Clinical Hospital No 4 in Lublin. The exclusion factor from further research was the diagnosis of a patient with hyperthyroidism. Conclusions. Atrial fibrillation is more common among male patients. With age, the number of patients with supraventricular arrhythmias is increasing. The most common method of restoring sinus rhythm is electrical cardioversion. Changes in atmospheric pressure ≥8 hPa have a significant effect on atrial fibrillation (p = 0.000506). Atmospheric conditions such as air humidity, wind speed, type and amount of precipitation, changes in air temperature, haze, presence of lightning did not have a statistically significant effect on the incidence of atrial fibrillation. The purpose of the study is to determine whether and how atmospheric conditions affect the occurrence of atrial fibrillation.